2019
DOI: 10.1080/21645515.2019.1638726
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and economic burden of varicella in the Middle East: a systematic literature review

Abstract: This systematic literature review was conducted to better understand the epidemiology and burden of varicella across the Middle East, gain insight into the evidence to support using universal varicella vaccination (UVV), and identify potential data gaps. Both epidemiology and economic data on the burden of varicella were limited and varied significantly. Most of the data focussed on varicella burden in the absence of a UVV program. In the absence of UVV, varicella incidence is increasing across this region wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 53 publications
(94 reference statements)
0
20
0
Order By: Relevance
“…Six countries in the Middle East use a universal varicella vaccination program, and in all but Oman, a 2-dose schedule is implemented. Both Qatar and the United Arab Emirates have vaccine coverage rates exceeding 90% [ 42 , 43 ].…”
Section: Varicella Vaccination Status By Regionmentioning
confidence: 99%
“…Six countries in the Middle East use a universal varicella vaccination program, and in all but Oman, a 2-dose schedule is implemented. Both Qatar and the United Arab Emirates have vaccine coverage rates exceeding 90% [ 42 , 43 ].…”
Section: Varicella Vaccination Status By Regionmentioning
confidence: 99%
“…The reviews that examined the impact of UVV, either regionally or countrywide, reported limited data on vaccination coverage rates; where they were reported, they did not necessarily correspond with the timeline of reported programme outcomes. Varied vaccination coverage data in individual studies was also reported in one included review and was highlighted as an area that requires further research 31 . The lack of vaccination coverage data alongside corresponding outcome data, limits the interpretation and understanding of the full impact of existing UVV programmes.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 13 reviews either did not conduct a risk of bias assessment of individual studies included in the review or where it was indicated that it was conducted, the tool used was not clear and results were not provided. [23][24][25][26][27][30][31][32][33][34][35][36][37] In seven of the 10 reviews that included a Italy Pooled analysis of epidemiological data from all eight Italian regions demonstrated significant reductions in incidence of varicella up to 9 years after two-dose UVV introduction. 9 In Sicily alone, varicella notifications decreased by over 95% between 2003 (when the two-dose schedule was introduced) and 2012.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…VZV is one of the common causes of childhood encephalitis 14 . Since incorporation of varicella vaccine to well-child immunization schedule in 2013, varicella-related hospitalizations and deaths has declined in Turkey 15 . This supports the evidence that varicella vaccine reduces severe complications from varicella infection.…”
Section: Discussionmentioning
confidence: 99%